Developmental exposure to diacetoxyscirpenol reversibly disrupts hippocampal neurogenesis by inducing oxidative cellular injury and suppressed differentiation of granule cell lineages in mice. (February 2020) - Nakajima, Kota; Ito, Yuko; Kikuchi, Satomi; Okano, Hiromu; Takashima, Kazumi; Woo, Gye-Hyeong; Yoshida, Toshinori; Yoshinari, Tomoya; Sugita-Konishi, Yoshiko; Shibutani, Makoto
Abstract: To investigate the developmental exposure effect of diacetoxyscirpenol (DAS) on postnatal hippocampal neurogenesis, pregnant ICR mice were provided a diet containing DAS at 0, 0.6, 2.0, or 6.0 ppm from gestational day 6 to day 21 on weaning after delivery. Offspring were maintained through postnatal day (PND) 77 without DAS exposure. On PND 21, neural stem cells (NSCs) and all subpopulations of proliferating progenitor cells were suggested to decrease in number in the subgranular zone (SGZ) at ≥ 2.0 ppm. At 6.0 ppm, increases of SGZ cells showing TUNEL +, metallothionein-I/II +, γ-H2AX + or malondialdehyde +, and transcript downregulation of Ogg1, Parp1 and Kit without changing the level of double-stranded DNA break-related genes were observed in the dentate gyrus. This suggested induction of oxidative DNA damage of NSCs and early-stage progenitor cells, which led to their apoptosis. Cdkn2a, Rb1 and Trp53 downregulated transcripts, which suggested an increased vulnerability to DNA damage. Hilar PVALB + GABAergic interneurons decreased and Grin2a and Chrna7 were downregulated, which suggested suppression of type-2-progenitor cell differentiation. On PND 77, hilar RELN + interneurons increased at ≥ 2.0 ppm; at 6.0 ppm, RELN-related Itsn1 transcripts were upregulated and ARC + granule cells decreased. Increased RELN signals may ameliorate the response to the decreases of NSCs and ARC-mediated synaptic plasticity. These results suggest that DAS reversibly disrupts hippocampal neurogenesis by inducing oxidative cellular injury and suppressed differentiation of granule cell lineages. The no-observed-adverse-effect level of DAS for offspring neurogenesis was determined to be 0.6 ppm (0.09–0.29 mg/kg body weight/day). Highlights: Maternal exposure effect of diacetoxyscirpenol (DAS) on offspring hippocampal neurogenesis was examined in mice. Neural stem cells (NSCs) and all progenitor cell populations were suggested to decrease at the end of exposure on weaning. Apoptosis due to oxidative DNA damage may be responsible for the reduction of NSCs and early-stage progenitor cells. A reduced number of PVALB + GABAergic interneurons may cause suppression of type-2 progenitor cell differentiation. Increased RELN signals at the adult stage may ameliorate the response to recover neurogenesis and synaptic plasticity.